NGARUAT CAI : SEBUAH PENGIKAT KEBERSAMAAN DI CIRATEUN - Mardotillah, Mila; S. Soemarwoto, Rini (HUMANIKA, 2017)
Cultural society lasted for revival by community. The symbolic meaning of a behavior that is reflected in a culture understood for generations. Water is one of the essential human needs for survival. Society used a symbol of water maintained as an effort conservation with the knowledge limitation of society itself. Ngaruat cai is a Sundanese traditional ceremony with the intention of thanksgiving and reinforcement refused for its society. This activity was conducted in order to maintain and grateful for the water received by Cirateun’s community as a cultural heritage. There is symbolic meaning from that’s activity with expectation that the same water need can bind society to participate actively.The purpose of this paper is to discuss the meaning of ritual symbols and social changes in Sundanese language. The method of this paper is qualitative ethnography to describe the activities of the Cirateun community to keep the Coblong river through symbolic Ngaruat Cai.Conclusion that the common perception in the symbolic ritual Ngaruat Cai can be a way to improve people's knowledge, people's needs not only maintain a water cleans but also how to keep clean water used and waste water must still be maintained and managed so as not to pollute other environment.